La reconstruction de l’université de Caen. À l’origine du campus français - Patrice Gourbin (In Situ)
After its destruction in 1944, the organization of the University of Caen was completely redesigned. For this occasion, the option of a university campus was carried out, for the first time in France. All facilities (teaching, research, student life) were brought together on a large ground of over 30 hectares on the outskirts of the city. The development of this new program was an opportunity to debate on the elements to be integrated, and to consider the possible interactions between the university and the city. The widely shared consensus view was that the future buildings should display monumental features. The fulfillment of the project had to take into account the context of rapid growth of the number of students and revealed some gap, but basic choices became confirmed : remoteness of the campus, monumental features of teaching and research buildings, landscaping of the park.